Insights into malaria susceptibility using genomewide data on 17,000 individuals from Africa, Asia and Oceania - Ghansah, A.K.; Sisay-Joof, F.; Sirugo, G.; d’Alessandro, U. (nature Communications, 2019)
The human genetic factors that affect resistance to infectious disease are poorly understood. Here we report a genome-wide association study in 17,000 severe malaria cases and population controls from 11 countries, informed by sequencing of family trios and by direct typing of candidate loci in an additional 15,000 samples. We identify five replicable associations with genome-wide levels of evidence including a newly implicated variant on chromosome 6. Jointly, these variants account for around one-tenth of the heritability of severe malaria, which we estimate as ~23% using genome-wide genotypes. We interrogate available functional data and discover an erythroid-specific transcription start site underlying the known association in ATP2B4, but are unable to identify a likely causal mechanism at the chromosome 6 locus. Previously reported HLA associations do not replicate in these samples. This large dataset will provide a foundation for further research on the genetic determinants of malaria resistance in diverse populations.
Research Article
Keywords: human genetic factors; infectious disease; genome-wide; erythroid-specific transcription